Sensitivity, Specificity and Predictive Value of Modified Assays for Activated Protein C Resistance in Children - Brandt, Greg; Gruppo, Ralph; Glueck, Charles J.; Stroop, Davis; Becker, Ann; Pillow, Ann; Wang, Ping (Thrombosis and Haemostasis, 1998)
Very little data is available assessing the clinical utility of coagulation-based APC resistance assays compared to DNA-based analysis for the factor V Leiden mutation in children. Therefore, the clinical utility of four aPTT-based assays for APC resistance was evaluated in 169 children, ages 3 months through 16 years. The prevalence of the Arg506 to Gln mutation was 7/169 (4.1%). Using cutoff points derived from the normal PCR-screened population (n = 162), two assays for APC resistance (APC-SR and n-APC-SR) gave poor concordance with the PCR assay (sensitivity 29% and 57%, respectively). Two modified assays (FDAPC-SR and n-FDAPC-SR), in which patient plasma was prediluted 1:5 in factor V deficient plasma, gave excellent concordance (sensitivity 100%). The predictive value of a positive test was 0.25, 0.44, 1.00 and 0.88 for the APC-SR, n-APC-SR, FDAPC-SR and n-FDAPC-SR, respectively. The FDAPC-SR and n-FDAPC-SR tests gave excellent discrimination using cutoff values derived from the total population (n = 169) without regard to previous PCR screening results.